Effectiveness of Suboccipital Soft Tissue Inhibition Technique Versus Neurodynamics On Tension Type Headache for Female Physiotherapy Students: Life Sciences-Physiotherapy - laxmi, V.Raja; Alshewaier, Shady Abdullah; Nazrin, L.; Unnikrishnan, Radhakrishnan; Shinuja, Omana (International Journal of Life Science and Pharma Research, 2022)
The intent of the study is to establish the effectiveness of suboccipital soft tissue inhibition technique versus neurodynamics on tension type headache for female physiotherapy students. Tension-Type Headache (TTH) is a symptom with a greater impact on quality of life and with a significant socioeconomic impact. Tension-Type Headache and stress are common in student. Long term headache can progress to chronic headache, which has a great impact on the daily life of patients, for instance; aspects of emotions, daily work, and general life activities and so on. Suboccipital Soft tissue mobilization reduces muscle tension and neural tension in tension type headache. The purpose of this study was to explore the application of sub-occipital soft tissue inhibition technique and neurodynamics to compare its effect on Tension-Type Headache. This experimental study included 30 female subjects with headache for more than 1 month and divided into three groups. Group A received suboccipital soft tissue inhibition. Group B received neurodynamics technique, Group C Received both suboccipital soft tissue inhibition and neurodynamic technique. Pre and Post test were taken using VAS, NDI, HDI, Cervical ROM after 4 weeks. On comparing mean values of Group A, Group B & Group C on Visual Analogue Scale score for pain intensity, it showed a significant decrease in the post test Mean values, but Suboccipital soft tissue inhibition and Neurodynamic Techniques (Group C) showed 2.63 which has a lower mean value and is more effective than Suboccipital soft tissue inhibition Technique (Group A) 3.61 and followed by Neurodynamic Technique (Group B) 3.86 at P = 0.001. Hence Null Hypothesis is rejected. This study and our study concludes that both suboccipital soft tissue inhibition and neurodynamics showed a positive impact on headache and quality of life among adults. Although results showed a clinical improvement, there is no clear evidence that one technique is superior to another, combination of both techniques is the most effective treatment.